Dietary nitrate intake is associated with muscle function in older women. Issue 3 (24th March 2019) - Sim, Marc; Lewis, Joshua R.; Blekkenhorst, Lauren C.; Bondonno, Catherine P.; Devine, Amanda; Zhu, Kun; Peeling, Peter; Prince, Richard L.; Hodgson, Jonathan M.
Abstract: Background: In younger individuals, dietary nitrate supplementation has been shown to improve short‐term vascular and muscle function. The role of higher habitual nitrate intake as part of a typical diet on muscle function in ageing has not been investigated. A cross‐sectional study of relationships between dietary nitrate and measures of muscle function in older community‐dwelling Australian women ( n = 1420, ≥70 years) was undertaken. Methods: Participants completed a semi‐quantitative food frequency questionnaire assessing dietary intake over the previous year. Total nitrate from vegetables and non‐vegetable sources was calculated from a validated instrument that quantified the nitrate content of food recorded within the food frequency questionnaire. Handgrip strength and timed‐up‐and‐go (TUG) were assessed, representing muscle strength and physical function, respectively. Cut‐points for weak grip strength (<22 kg) and slow TUG (>10.2 s) were selected due to their association with adverse outcomes. Linear and logistic regressions were used to examine the relationship between total nitrate intake and muscle function measures. Results: Mean ± standard deviation (SD) total nitrate intake was 79.5 ± 31.2 mg/day, of which 84.5% came from vegetables. Across the unadjusted tertiles of nitrate intake (<64.2 mg/day; 64.2 to <89.0 mg/day; ≥89.0 mg/day), women in the highest tertile had a 4% stronger grip strength and a 5% faster TUG performance compared with the lowest tertile. In multivariable‐adjusted models, each SD higher nitrate intake (31.2 mg/day) was associated with stronger grip strength (per kilogram, β 0.31, P = 0.027) and faster TUG (per second, β −0.27, P = 0.001). The proportion of women with weak grip strength (<22 kg) or slow TUG (>10.2 s) was 61.0% and 36.9%, respectively. Each SD higher nitrate intake (31.2 mg/day) was associated with lower odds for weak grip strength (OR 0.84, 95% CI 0.74–0.95, P = 0.005) and slow TUG (OR 0.86, 95% CI 0.76–0.98, P = 0.021). Compared with women in the lowest tertile of nitrate intake, women in the highest nitrate intake tertile had lower odds for weak grip strength (OR 0.65, 95% CI 0.49–0.87, P trend= 0.004) and slow TUG (OR 0.72, 95% CI 0.53–0.97, P trend = 0.044). Conclusions: This investigation highlights potential benefits of nitrate‐rich diets on muscle strength and physical function in a large cohort of older women. Considering poor muscle strength and physical function is associated with a range of adverse health outcomes such as falling, fractures, cardiovascular disease, and mortality, increasing dietary nitrate, especially though vegetable consumption may be an effective way to limit age‐related declines in muscle function.